Answer:(x^2+y^2)^2=(x^2+y^2)(x^2+y^2)
Step-by-step explanation:
We can rewrite left side into right side form
(x^2+y^2)^2=(x^2+y^2)(x^2+y^2)
we can expand it
(x^2+y^2)^2=x^4+x^2y^2+x^2y^2+y^4
(x^2+y^2)^2=x^4+y^4+2x^2y^2
we can add and subtract 2x^2y^2
(x^2+y^2)^2=x^4+y^4+2x^2y^2+2x^2y^2-2x^2y^2
(x^2+y^2)^2=x^4-2x^2y^2+y^4+2x^2y^2+2x^2y^2
(x^2+y^2)^2=x^4-2x^2y^2+y^4+4x^2y^2
(x^2+y^2)^2=x^4-2x^2y^2+y^4+(2xy)^2
(x^2+y^2)^2=(x^2-y^2)^2+(2xy)^2
Answer:
the answer would be y=2x+4
Step-by-step explanation:
Answer:
Step-by-step explanation:
Five equivalent ratios:
7:8 = 14:16
= 21:24
= 70:80
= 49:56
= 35:40
Answer:
Step-by-step explanation:
Since all 3 of these angle come off a straight line, they all add up to equal 180. Thus,
2j + 32 + 6j - 2 + 30 = 180 and
8j + 60 = 180 and
8j = 120 so
j = 15
Answer:
Explanation:
m = (y1 - y)/(x1 - x)
y1 = 50, y = 90
x1 = 2, x = 4
m = (50 - 90)/(2 - 4)
m = -40/-2
m = 20
b is the y intercept = 50
So our equation is written as:
y = 20x + 50